2009
DOI: 10.1158/0008-5472.can-08-3807
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell IFN-γ Levels Predict Long-term Survival with Imatinib Mesylate Therapy in Gastrointestinal Stromal Tumor–Bearing Patients

Abstract: Clinical outcomes of gastrointestinal stromal tumor (GIST)-bearing patients treated with imatinib mesylate (IM) are variable. Other than the site of mutation within the c-kit gene, prognostic features of GIST remain undefined. IM can exhibit off-target effects such as triggering natural killer (NK) cell activity. We addressed whether NK cell functions could predict long term survival with IM. NK cell functions were followed up in 77 GIST patients enrolled onto two phase III trials. ''Immunologic responders'' w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
137
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(147 citation statements)
references
References 48 publications
7
137
1
2
Order By: Relevance
“…Potential immune prognostic/predictive parameters have been more recently reported. In metastatic patients treated with imatinib, the NK-cell IFNg production after 2 months of treatment 18 and an alternative transcript of NKp30 gene 19 were predictors for survival. In localized GIST, a low blood neutrophil-to-lymphocyte ratio was an independent favorable prognostic parameter, 54 as were strong tumor infiltrates of CD3 C T cells and of NK cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential immune prognostic/predictive parameters have been more recently reported. In metastatic patients treated with imatinib, the NK-cell IFNg production after 2 months of treatment 18 and an alternative transcript of NKp30 gene 19 were predictors for survival. In localized GIST, a low blood neutrophil-to-lymphocyte ratio was an independent favorable prognostic parameter, 54 as were strong tumor infiltrates of CD3 C T cells and of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Second, their presence and/or activation have been associated with prognosis 16 and/or response to imatinib. 14,18,19 Third, and as observed with certain chemotherapy drugs, 20 the antitumor action of imatinib is also due in part to indirect effects on immune cells, notably NK cells; 21 and CD8 C T cells 14 ; in the same line, the concurrent CTLA-4 blockade augments the efficacy of imatinib in mouse GIST by increasing IFNg-producing CD8 C T cells. 14 Finally, by contrast with targeted therapies, immunotherapy can adapt to the emergence of resistant clones thanks to the high adaptability of the immune response.…”
Section: Introductionmentioning
confidence: 95%
“…The use of NK cell IFN-g secretion capacity as a surrogate marker for NK cell activity is becoming increasingly popular and has already been designated as a positive prognostic marker in chronic myeloid leukemia 71 and gastrointestinal stromal tumors. 72,73 Also for adult acute leukemia it has been suggested that impaired NK cell cytokine production is associated with early relapse regardless of remission status. 20 Moreover, several recent studies indicate that the potency of NK cells to secrete IFN-g is depressed in AML patients resulting in deprived immune responses (Table 1).…”
Section: Nk Cell Immune Escape In Aml E Lion Et Almentioning
confidence: 99%
“…This indicates that, in patients, it may lead to impaired classical activation of macrophages helpful in removing tumor cells. This is further strengthened by a recent study in patients with gastrointestinal tumor under Imatinib Mesylate [46]. NK cell IFN-γ levels predict the long-term survival of these cancer patients [46].…”
Section: Classically Activated Macrophages (M1 Macrophages)mentioning
confidence: 89%
“…This is further strengthened by a recent study in patients with gastrointestinal tumor under Imatinib Mesylate [46]. NK cell IFN-γ levels predict the long-term survival of these cancer patients [46]. Increased survival of these patients with higher IFN-γ levels upon Imatinib Mesylate treatment shows that IFN-γ exhibits its tumoricidal effect by activating the residential macrophages in tumor microenvironment and activation of direct antitumor action NK cells.…”
Section: Classically Activated Macrophages (M1 Macrophages)mentioning
confidence: 92%